Generalized Permuting 3-Derivations of Prime Rings - Faraj, Anwar K.; Shareef , Sabreen J. (Iraqi Journal of Science, 2022)
This work generalizes Park and Jung's results by introducing the concept of generalized permuting 3-derivation on Lie ideal.